Hubungan Dukungan Suami dengan Pemberian Asi Ekslusif di Puskesmas Danurejan I Kota Yogyakarta - Yohana Klaravina; Setyo Retno Wulandari Wulan (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: Based on data from the World Health Organization, globally around 44% of infants aged 0-6 months are exclusively breastfed (WHO, 2020). . Nationally, based on data from the Ministry of Health of the Republic of Indonesia, the coverage of infants receiving exclusive breastfeeding in 2018 was 68.74% and there was a decrease in exclusive breastfeeding coverage in 2019 which was 67.74%. Meanwhile, according to the Provincial Health Profile of D.I. Yogyakarta in 2020, Sleman Regency occupies the highest position in the coverage of exclusive breastfeeding, which is 85.00% and the City of Yogyakarta occupies the highest position with the coverage of exclusive breastfeeding at 73.25%. Method: This research is a quantitative study, this study uses an analytical observational method with a cross sectional research design. The total population is 124. Sampling using accidental sampling, obtained the number of respondents as many as 55. The data analysis used is the Chi Square statistical test. Result: The frequency distribution of husband's support in exclusive breastfeeding is in the supportive category as many as 47 respondents (85.5%). The frequency distribution of exclusive breastfeeding is in the exclusive breastfeeding category as many as 41 respondents (74.5%). The frequency distribution of husband's support and exclusive breastfeeding was 39 respondents (70.9%). The frequency distribution of husbands did not support and was not given exclusive breastfeeding as many as 8 respondents (14.5%). Chi-Square results obtained a significant value of 0.002. Conclusion: There is a Relationship between Husband's Support and Exclusive Breastfeeding in the Work Area of Danurejan I Public Health Center, Yogyakarta City.